Authority and Language in the Encomium Emmae Reginae. Issue 1 (2nd January 2020) - Butler, Emily
ABSTRACT: This article resuscitates the agency of Queen Emma through examining signs of her influence in the creation of the Encomium Emmae Reginae . While she was not the author of the text, she was more than a patron and seems to have directed and influenced the composition of the text in ways that were intended to cultivate greater power and even authority at court. References to her first husband, King Æthelred, are suppressed, leading at times to the implication that Alfred, Edward, and Harthacnut all have the same father. At the same time, the Encomium clearly draws a line between her children and Harold Harefoot, Cnut's son from a prior relationship. Emma's efforts at crafting a literary legacy for her family seem to have been emulated by Edith in the Vita Ædwardi, and this influence shows how relationships between women can affect literary culture and production.